IL-7 promotes T cell proliferation through destabilization of p27(Kip1) - Li, Wen Qing (The Rockefeller University Press, 2006)

(untitled)
Interleukin (IL)-7 is required for survival and homeostatic proliferation of T lymphocytes. The survival effect of IL-7 is primarily through regulation of Bcl-2 family members; however, the proliferative mechanism is unclear. It has not been determined whether the IL-7 receptor actually delivers a proliferative signal or whether, by promoting survival, proliferation results from signals other than the IL-7 receptor. We show that in an IL-7–dependent T cell line, cells protected from apoptosis nevertheless underwent cell cycle arrest after IL-7 withdrawal. This arrest was accompanied by up-regulation of the cyclin-dependent kinase inhibitor p27(Kip1) through a posttranslational mechanism. Overexpression of p27(Kip1) induced G1 arrest in the presence of IL-7, whereas knockdown of p27(Kip1) by small interfering RNA promoted S phase entry after IL-7 withdrawal. CD4 or CD8 T cells transferred into IL-7–deficient hosts underwent G1 arrest, whereas 27(Kip1)-deficient T cells underwent proliferation. We observed that IL-7 withdrawal activated protein kinase C (PKC)θ and that inhibition of PKCθ with a pharmacological inhibitor completely blocked the rise of p27(Kip1) and rescued cells from G1 arrest. The conventional pathway to breakdown of p27(Kip1) is mediated by S phase kinase-associated protein 2; however, our evidence suggests that PKCθ acts via a distinct, unknown pathway inducing G1 arrest after IL-7 withdrawal from T cells. Hence, IL-7 maintains T cell proliferation through a novel pathway of p27(Kip1) regulation.